Effect of Malaysian anti-diabetic plant extracts on adipocyte cells - Ali, Mohamed Zaffar; Bakhtiar, M. Taher; Darnis, Deny Susanti (2010)
Diabetic mellitus (DM)is a disease of worldwide significance and increasing prevalence. It is a metabolic disorder characterized by a predisposition to developing significantly raised blood glucose. The objective of this research was to evaluate the antidiabetic properties of medicinal plants ued in the treatment if type 2 diabetes. The selection of the plants was based on traditional reputation of usefulness in treating diabetes.Ethanolic extracts of Andrographis paniculata, Cinnamomum zeylanicum, Lagerstroemia speciosa, Momodica charantia, Orthosiphon stamineus, Phyllanthus amarus, Pithecellobium jiringa, Syzgium polyanthum, and Tinospora cirspa were selected. Insulin was used as a postive control. The plants were studied on the bioactive peptides (adipokines) using an in vitro model. Cells were seeded and counted everyday for ten days. The first step was to test the ability of the plants to induce predipocytes to adipocyte.cells. Prior to the testing, preadipocytes (3T3-L1) cells were differentiated to adipocytes by using a mixture of dexamethasone, isobutlymethylxanthine and the plant extract. Treated cells were stained by usingg oil red ) and the absorbance was read at 340 nm. 3T3-L1 preadipocytes exhibited the maximum growth at day-four(4.7x105 cells. Oil red O staining results showed that C.zeylanicum, L.speciosa leaves and S.polyanthum extracts have strong activity in inducing lipid formation and the others have moderate properties. The results of the study suggest the validiy of the plants for clinical usein treatmentof type 2 diabetes, after their toxicological investigation. This finding may lead to seriousresearch towardsa developing new and efficient drugs for diabetes.